A systematic literature review of empirical studies on tertiary EFL teachers’ motivation and demotivation - Nousin Laila Bristi; Latisha Asmaak Shafie; Hafizah Binti Hajimia; Md. Kamrul Hasan (Cogent Education)
The 21st-century higher education complexities have given rise to the necessities of conducting empirical studies related to EFL teachers’ motivation and demotivation. This necessitates the researchers identifying the key motivational features and research practices in the domain. Hence, this Systematic Literature Review encompassed empirical studies on university EFL teachers’ motivation and demotivation between 1974 and 2024. The researchers extracted articles from Web of Science and Scopus databases that were screened for eligibility, utilizing the PRISMA protocol which yielded 21 empirical papers. The selected articles were analyzed with an integrative approach. The qualitative data included the salient discoveries of the empirical studies, and the quantitative data encompassed the methodological features. The qualitative themes were aligned with the quantitative numbers during the quantitative data analysis to build deeper insights. The qualitative results revealed emerging themes, like university EFL teachers’ motivation and demotivation for research, innovative teaching, professional development, teaching English, and career choice. Quantitative findings showcased the inadequacy of empirical studies that concern time, places, topics, theories, and methodologies. The study prescribes several measures for policymakers, university EFL teachers, and teacher-researchers.